2013
DOI: 10.1111/acel.12082
|View full text |Cite
|
Sign up to set email alerts
|

Low hydrogen peroxide production in mitochondria of the long‐lived Arctica islandica: underlying mechanisms for slow aging

Abstract: SummaryThe observation of an inverse relationship between lifespan and mitochondrial H 2 O 2 production rate would represent strong evidence for the disputed oxidative stress theory of aging. Studies on this subject using invertebrates are surprisingly lacking, despite their significance in both taxonomic richness and biomass. Bivalve mollusks represent an interesting taxonomic group to challenge this relationship. They are exposed to environmental constraints such as microbial H 2 S, anoxia/reoxygenation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 43 publications
4
34
0
Order By: Relevance
“…An additional finding that contradicts the rate of living theory is that peak metabolic rate during flight is positively, rather than negatively correlated with lifespan in M. cinxia (Niitepõld & Hanski, 2013). Furthermore, ROS production is highly variable among tissues and species and is apparently not directly proportional to metabolic rate (Hulbert et al, 2007;Robert et al, 2007;Burton et al, 2011;Boardman et al, 2012;Selman et al, 2012;Speakman & Garratt, 2014; but see Hou, 2013) or in some cases to longevity as well (Lewis et al, 2012;Montgomery, Hulbert & Buttemer, 2012a; but see Archer et al, 2012;Munro et al, 2013), thus undermining a key proposed link between metabolic rate and longevity, although other mechanisms may be involved (Van Raamsdonk et al, 2010;Pulliam, Bhattacharya & Van Remmen, 2012). The cave salamander Proteus anguinus Laurenti highlights this problem because it has an unusually long lifespan (mean = 68.5 years), despite having a small body size (15-20 g), and an unexceptional metabolic rate and levels of antioxidant activity and age-related cellular damage (Voituron et al, 2011).…”
Section: (4) Ageingmentioning
confidence: 95%
See 1 more Smart Citation
“…An additional finding that contradicts the rate of living theory is that peak metabolic rate during flight is positively, rather than negatively correlated with lifespan in M. cinxia (Niitepõld & Hanski, 2013). Furthermore, ROS production is highly variable among tissues and species and is apparently not directly proportional to metabolic rate (Hulbert et al, 2007;Robert et al, 2007;Burton et al, 2011;Boardman et al, 2012;Selman et al, 2012;Speakman & Garratt, 2014; but see Hou, 2013) or in some cases to longevity as well (Lewis et al, 2012;Montgomery, Hulbert & Buttemer, 2012a; but see Archer et al, 2012;Munro et al, 2013), thus undermining a key proposed link between metabolic rate and longevity, although other mechanisms may be involved (Van Raamsdonk et al, 2010;Pulliam, Bhattacharya & Van Remmen, 2012). The cave salamander Proteus anguinus Laurenti highlights this problem because it has an unusually long lifespan (mean = 68.5 years), despite having a small body size (15-20 g), and an unexceptional metabolic rate and levels of antioxidant activity and age-related cellular damage (Voituron et al, 2011).…”
Section: (4) Ageingmentioning
confidence: 95%
“…Moreover, recent statistical analyses have shown that maximal lifespan in various vertebrates is unrelated to resting metabolic rate after controlling for differences in body size and taxonomic affinity (Speakman, 2005;de Magalhães, Costa & Church, 2007;Robert, Brunet-Rossinni & Bronikowski, 2007;Valencak & Ruf, 2007;Furness & Speakman, 2008;Montgomery, Hulbert & Buttemer, 2012b). Furthermore, ROS production is highly variable among tissues and species and is apparently not directly proportional to metabolic rate (Hulbert et al, 2007;Robert et al, 2007;Burton et al, 2011;Boardman et al, 2012;Selman et al, 2012;Speakman & Garratt, 2014; but see Hou, 2013) or in some cases to longevity as well (Lewis et al, 2012;Montgomery, Hulbert & Buttemer, 2012a; but see Archer et al, 2012;Munro et al, 2013), thus undermining a key proposed link between metabolic rate and longevity, although other mechanisms may be involved (Van Raamsdonk et al, 2010;Pulliam, Bhattacharya & Van Remmen, 2012). An additional finding that contradicts the rate of living theory is that peak metabolic rate during flight is positively, rather than negatively correlated with lifespan in M. cinxia (Niitepõld & Hanski, 2013).…”
Section: (4) Ageingmentioning
confidence: 99%
“…This excess can enhance oxygen affinity [49,50], regulate the redox state [51], and preserve the oxidized state of upstream ETS complexes [52]. Bivalves are often subject to wide changes in oxygen availability in the intertidal zone or in burrows [53], and the upregulation of CIV has been described during conditions where O 2 is scarce [54]. The maintenance of a high CIV excess capacity in bivalves could improve kinetic trapping of O 2 during hypoxic conditions and decrease the reducing charge stored in the upstream ETS enzymes and the consequent potential burst of ROS production during reoxygenation [52].…”
Section: (B) Intraspecific Analysesmentioning
confidence: 99%
“…This differs from the expression pattern seen for S. glomerata transcripts which are part of the mitochondrial respiratory chain, where NADH dehydrogenase [ubiquinone] iron-sulfur protein 2 (complex I protein), cytochrome b-c1 complex subunit 7 (complex III protein) and alternative oxidase were 4-fold and higher up-regulated and cytochrome c oxidase subunit 5A mitochondrial (complex IV protein) 4-fold and higher down-regulated in the elevated treatment when compared to control oysters (Additional file 7: Table S2). Both, complex I and complex III are considered to be the major sources of ROS production in the mitochondrial respiratory chain [65,66], suggesting that upregulation of mitochondrial respiration in CO 2 challenged S. glomerata would lead to an increase in ROS production, elevating the risk of oxidative damage to the tissues of the oysters. However, this appears to be counteracted by two measures in the S. glomerata exposed to the elevated CO 2 treatment.…”
Section: Respiration and Antioxidant Defencementioning
confidence: 99%
“…However, this appears to be counteracted by two measures in the S. glomerata exposed to the elevated CO 2 treatment. Firstly, alternative oxidase (Additional file 7: Table S2), located in the inner mitochondrial membrane, allows the animal to circumvent complex III by transferring electrons from coenzyme Q to oxygen and therefore limits the amount of ROS produced during cellular respiration [66,67]. Secondly, ROS originating from complex I are thought to be removed by mitochondrial matrix antioxidants such as glutathione peroxidase and catalase [65].…”
Section: Respiration and Antioxidant Defencementioning
confidence: 99%